Comparative energy analysis of R1234yf, R1234ze, R717 and R600a in Vapour Compression Refrigeration system as replacement of R134a. (2022) - Soni, Shubham; Mishra, Punit; Maheshwari, Govind; S.Verma, Devendra
Abstract: In this study effect of utilization of refrigerants with low Global warming potential is studied theoretically based on first law of thermodynamics and mass balance. Refrigerants like R1234yf, R1234ze, R717, and R600a are used instead of R134a in the Vapour Compression Refrigeration system of 1 TR. The Global Warming Potential of all the refrigerants is negligible (below 4) as compared to that of R134a (1300). The results obtained show that R1234ze and R600a are better refrigerants in the context of COP and power consumed as compared to R134a. Other refrigerants are not very behind and obtain a COP value comparable to that of R134a. R1234yf and R717 may consume slightly more power but their low Global Warming Potential makes them a decent option. R717 requires the least mass flow rate as compared to all the chosen refrigerants.